2015
DOI: 10.1021/acscatal.5b01562
|View full text |Cite
|
Sign up to set email alerts
|

On Oxygen Activation at Rutile- and Anatase-TiO2

Abstract: The rutile form of titanium dioxide (r-TiO 2 ) usually shows a photocatalytic activity lower than that of anatase-TiO 2 (a-TiO 2 ). Nevertheless, there are numerous examples of sometimes unexpectedly high activity of r-TiO 2 . This material may appear to be particularly useful when a noncomplete and selective photocatalytic oxidation of organic substrates is required. On the basis of literature examples and our own studies, we compare the photocatalytic activities of r-TiO 2 , a-TiO 2 , and r-TiO 2 /a-TiO 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
106
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 63 publications
12
106
0
3
Order By: Relevance
“…On the basis of the former, the participation of H 2 O oxidation in the product formation, and the absence of O 2 in the gas phase of the photoreactor, it might be possible that O 2 or O‐derived species remain on the surface of the photocatalyst instead of being desorbed. Potential O‐derived species could be superoxide or surface peroxyl species . Another likely reason for the absence of O 2 in the gas‐phase of the photoreactor could be incomplete H 2 O oxidation [Equations ] or H 2 O reduction [Equation ].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the former, the participation of H 2 O oxidation in the product formation, and the absence of O 2 in the gas phase of the photoreactor, it might be possible that O 2 or O‐derived species remain on the surface of the photocatalyst instead of being desorbed. Potential O‐derived species could be superoxide or surface peroxyl species . Another likely reason for the absence of O 2 in the gas‐phase of the photoreactor could be incomplete H 2 O oxidation [Equations ] or H 2 O reduction [Equation ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we described anatase (a-TiO 2 ) and rutile (r-TiO 2 ) band alignment by using spectroelectrochemical method (−1.14 and −1.53 V vs. Ag/AgCl for a-TiO 2 and r-TiO 2 , respectively) [45]. Using the same method we estimated the potential of brookite band position to −1.2 V vs. Ag/AgCl [46].…”
Section: Resultsmentioning
confidence: 99%
“…48 Recent studies have also revealed an increase in photoactivity in TiO 2 samples that exhibit a mixture of anatase and rutile TiO 2 phases due to electron transfer from the rutile states to the anatase states which are lower in energy or vice versa. 49 Fig . 3A and B show the respective SEM and TEM images of C/ Cu 2 O NNs synthesized using 10 mg mL À1 dextrose.…”
Section: Resultsmentioning
confidence: 99%